Pengaruh Penambahan Serat Purun Terhadap Kuat Tekan Beton - Hendra Apriadi; Fameira Dhiniati (JURNAL ILMIAH BERING'S, 2016)
This study aimed to determine the compressive strength of concrete with the addition of fiber purun percentage of 5%, 7%, 10% by weight of cement. Based on the results of research conducted in laboratory obtained the following results: compressive strength average normal concrete amounted to 175.20 kg / cm2, while the compressive strength of the average concrete with the addition of fiber purun 5% at 173.20 kg / cm, the compressive strength of the average concrete with the addition of fiber purun 7% at 165.50 kg / cm2, the average compressive strength of concrete with the addition of fiber purun 10% of 163.58 kg / cm2. Thus, the average compressive strength of concrete plus fiber purun decreased compared to normal concrete, which for the addition of fiber purun percentage decreased 5% to 5.54%, while the percentage increment of fiber purun 10% decreased 6.63%.